(untitled) (World Bulletin of Public Health, 2025)
Lipocalin-2 (LCN2), also known as neutrophil gelatinase-associated lipocalin (NGAL), is a protein that plays a role in inflammation, immunity, and various physiological processes. It is part of the lipocalin family, which includes proteins that bind small hydrophobic molecules like lipids and steroids.NGAL is involved in innate immunity by sequestering iron and preventing its use by bacteria, thus limiting their growth. It is expressed in neutrophils and in low levels in the kidney, prostate, and epithelia of the respiratory and alimentary tracts. NGAL is used as a biomarker of kidney injury LCN2 is widely expressed across various tissues, including immune cells, bone, adipose tissue, liver, kidneys, lung, spleen, and epithelial cells, and exhibits sex- and fat depot-specific expression patterns. Structurally, LCN2 contains a hydrophobic lipidbinding pocket and glycosylation sites, enabling it to interact with diverse ligands and form dimers. In innate immunity, LCN2 plays a critical role by sequestering iron-laden siderophores, thereby restricting bacterial growth. Beyond its role in infection control, LCN2 is implicated in metabolic inflammation and diseases such as obesity and diabetes. Recent research has highlighted a pivotal role for LCN2 in mitochondrial phospholipid metabolism and mitochondrial function. In metabolic diseases and mitochondrial metabolism, LCN2 appears to display paradoxical effects. While some studies link it to improved insulin sensitivity, glucose regulation, and mitochondrial function, others associate it with insulin resistance, obesity, and mitochondrial dysfunction. These inconsistencies may arise from differences in experimental conditions and study populations